Upland Geopolitics Postwar Laos and the Global Land Rush - Dwyer, Michael B. (University of Washington Press, 2022)
Cold War legacies in Southeast Asia enable new geographies of enclosure In the twenty-first century, land deals in the Global South have become increasingly prevalent and controversial. Transnational access to arable land in impoverished "land-rich" countries in Latin America, Sub-Saharan Africa, and Southeast Asia highlights the link between the shifting geopolitics of economic development and problems of food security, climate change, and regional and international trade. Drawing on ethnographic and archival research, Upland Geopolitics uses the case of Chinese agribusiness investment in northern Laos to study the unbalanced geography of the new global land rush. Connecting the current rubber plantation boom to a longer trajectory of foreign intervention in the region, Upland Geopolitics reveals how legacies of Cold War conflict continue to pave the way for transnational enclosure in a socially uneven landscape.